CORELLATION BETWEEN KNOWLEDGE LEVEL WITH HIV/AIDS PREVENTION BEHAVIOR AT YADIKA 8 JATIMULYA VOCATIONAL SCHOOL IN 2022 - Desnitamutia, Desnita Mutia Sari; Rotua Suriany Simamora; Nurti Y. K. Gea (Rena Cipta Mandiri, 2023)
Background: The HIV/AIDS epidemic is a problem in Indonesia which is the 5th most at risk of HIV/AIDS in Asia, reports of HIV cases have increased every year since it was first reported in 1987, the most spike in increase was in 2016 compared to 2015 namely of 10,315 cases. Researcher's Objective: To find out the relationship between knowledge level and HIV/AIDS prevention behavior in Yadika 8 Jatimulya Vocational High School in 2022 Research Method: This research method is quantitative by using a cross sectional design. The population in this study were 110 teenagers at SMK Yadika 8 Jatimulya consisting of grades 10, 11 and 12 majoring in Accounting, Administration and Computer and Network Engineering. by using simple random sampling technique. Researcher results: Based on the results of research conducted by researchers at SMK Yadika 8 Jatimulya, the results of data processing using SPSS obtained Chi Square statistical test results, namely the Asymp Significance value (0.000) < value (0.05), this indicates that H0 is rejected. this shows that H0 is rejected. Thus, it can be concluded that there is a relationship between the level of knowledge and HIV/AIDS prevention behavior at SMK Yadika 8 Jatimulya in 2022. Conclusion: There is a relationship between the level of knowledge with HIV/AIDS prevention behavior in SMK Yadika 8 Jatimulya.